Long -Term Vegetation Dynamics over the Bani River Basin as Impacted by Climate Change and Land Use - Traore, Souleymane Sidi (2015)
A Thesis submitted to the Department of Civil Engineering College of Engineering in partial fulfilment of the requirement for the degree of DOCTOR OF PHILOSOPHY in Climate Change and Land Use April, 2015